Metodologías de diseño arquitectónico: una reflexión histórica para la elaboración del proceso creativo (2017)
The present article sets up a timeline in which the processes pertaining to architectural design are placed, thus defining the historical moment in which architectural design methodological processes are framed, thus allowing for the definition of the basic principles to approach architectural spatial creation. From the Vitruvian treatise, different architectural styles spanning from the classic, the renaissance and the modern and its subsequent influence in regards to the Colombian context, frame this research project as it finds common ground in the development of a design method which allows for the reflexive exercise of architectural design, far from subjectivity and, otherwise, close to an objective practice of architecture.